Drug trials on minors in long-term care at the Bethel Foundation from 1949 to 1975 - Rating, Dietz; Lenhard-Schramm, Niklas; Reuner, Gitta; Rotzoll, Maike (Clinical epileptology, 2023)
Triggered by reports of drug trials on minors in homes and medical facilities, the Directory Board of the von Bodelschwingh Foundation Bethel commissioned an investigation into whether Bethel carried out drug trials on minors and whether the legal framework was observed. Between 1949 and 1975, 2741 minors were cared for in the long-term care at Bethel for longer than six months. From this, a representative random sample of 256 patients was drawn for the study and their records were analyzed in detail. In 44 patients (16.6%), antiepileptic drugs were tested a total of 55 times. 28 psychopharmacological drugs were tested on 23 patients (8.7%). Overall, drug tests were carried out on 23.8% of the patients, particularly frequently in the years 1955 to 1966. During this period, approximately one-third of long-term care patients were treated with investigational drugs. Although there was extensive correspondence with the caregivers on many other medical and pedagogical issues in the records, in no case a written informed consent or written information regarding the drug tests was found. It can be assumed, and in some cases can traced back to the records, that the families were informed about the use of investigational drugs over the course. However, it can be assumed that most parents were neither informed about the treatment in advance nor that their written consent was obtained, although this would have been required under the legal and ethical rules in force at the time. The use of investigational drugs on minors was thus handled in Bethel in the same way as in other facilities. In Bethel, as an increasingly recognized epilepsy research centre, the focus on the testing of antiepileptic drugs was to an unprecedented extent.